The association between sex hormones and prevalence of OA in US adults - Tian, Xiaoyuan; Zhang, Bocheng (Frontiers in Medicine, 2024)
BackgroundAge and gender are commonly recognized as risk factors for osteoarthritis (OA), implying a potential association between sex hormones and OA pathogenesis. However, the precise role of sex hormones in OA remains elusive. Meanwhile, testosterone to estradiol (TT/E2) ratio is a new biomarker of sex hormone milieu. In this study, we aimed to investigate the relationship between sex hormones, specifically TT/E2 ratio, and the prevalence of OA among adults in the United States.MethodsThis study is a cross-sectional study, and the data sourced from the National Health and Nutrition Examination Survey (NHANES) 2013–2016 cycles. This study primarily focuses on individuals aged 50 and above, employing multivariable logistic regression to examine the association between sex hormones and OA.ResultsWe included 2,615 participants (972 females). No significant association was observed between testosterone or estradiol levels and OA prevalence when analyzed separately. However, the TT/E2 ratio exhibited a robust inverse association with OA, particularly in females (adjusted OR = 0.61, 95% CI: 0.41–0.91, p = 0.02). A nonlinear relationship was observed in females, with a threshold effect indicating reduced OA risk when the TT/E2 ratio exceeded 0.3.ConclusionThe TT/E2 ratio was inversely associated with OA risk, with a stronger and more consistent effect observed in females. These findings suggest the TT/E2 ratio as a potential biomarker for OA risk stratification, particularly in postmenopausal females. Future longitudinal studies are warranted to clarify the causal role of the TT/E2 ratio in OA.